2016
DOI: 10.1016/j.freeradbiomed.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Nrf2 is involved in FGF21-mediated fenofibrate protection against type 1 diabetic nephropathy

Abstract: The lipid lowering medication, fenofibrate (FF), is a peroxisome proliferator-activated receptor-alpha (PPARα) agonist, possessing beneficial effects for type 2 diabetic nephropathy (DN). We investigated whether FF can prevent the development of type 1 DN, and the underlying mechanisms. Diabetes was induced by a single intraperitoneal injection of streptozotocin in C57BL/6J mice. Mice were treated with oral gavage of FF at 100mg/kg every other day for 3 and 6 months. Diabetes-induced renal oxidative stress, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 51 publications
9
77
0
Order By: Relevance
“…The kidney has been identified as a target of FGF21, and exogenous administration of FGF21 protein has been shown to improve systemic metabolism and exert antifibrotic properties in kidneys of db/db mice (16). More recently, it has been demonstrated that upregulation of renal FGF21 expression in streptozotocin-treated C57/BL mice leads to a significant renal protection, believed to be due to PI3K/Akt/GSK3β/Fyn-mediated activation of the Nrf2 antioxidative pathway (32). In this study we identified significant upregulation of renal FGF21 mRNA in MR-fed females, in addition to increased expression of the FGF21 co-receptor, β-Klotho.…”
Section: Discussionsupporting
confidence: 55%
“…The kidney has been identified as a target of FGF21, and exogenous administration of FGF21 protein has been shown to improve systemic metabolism and exert antifibrotic properties in kidneys of db/db mice (16). More recently, it has been demonstrated that upregulation of renal FGF21 expression in streptozotocin-treated C57/BL mice leads to a significant renal protection, believed to be due to PI3K/Akt/GSK3β/Fyn-mediated activation of the Nrf2 antioxidative pathway (32). In this study we identified significant upregulation of renal FGF21 mRNA in MR-fed females, in addition to increased expression of the FGF21 co-receptor, β-Klotho.…”
Section: Discussionsupporting
confidence: 55%
“…Nrf2 plays a critical role in the cellular response to oxidative stress 25, 26 . Because increased CXCR7 expression decreased both ox-LDL-and HG-induced oxidative stress, we tested whether CXCR7 upregulation activate Nrf2 and its downstream target genes.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies showing that the Akt/GSK-3β/Fyn pathway plays a pivotal role in regulation of Nrf2 nuclear export and degradation 25, 29, 30, 45, 46 . Based on those studies and Akt phosphorylation results, we hypothesized that SDF-1/CXCR7 signaling activates Nrf2 via the Akt/GSK-3β/Fyn pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 gene deletion further enhances the pathological damage while rFGF21 replenishment significantly prevents it [7, 8, 91]. Fenofibrate protects against type 1 DN by FGF21-mediated upregulation of the nuclear factor E2-related factor 2 (Nrf2) antioxidant pathway [92]. In cisplatin-induced acute kidney injury (AKI), silencing of FGF21 aggravated tubular cell injury, whereas supplementation of rFGF21 protected against cisplatin nephrotoxicity [7, 8, 93].…”
Section: Fgf21 In Preclinical Experimental Animal Studiesmentioning
confidence: 99%